Undergraduate Students’ Metacognitive Awareness and Grammar Achievement - Amin Kurdi; Mohammad Adnan Latief; Utari Praba Astuti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: This paper aims to find out the correlation between metacognitive awareness and grammar achievement. It employs the correlational design and involves 87 first- semester undergraduate students of English Department. The result reveals that there is a significant positive correlation between students’ level of metacognitive awareness and their grammar achievement. It is also found that evaluation is the most dominant positive predictor in predicting students’ grammar achievement.Abstrak: Artikel ini bertujuan untuk mengetahui korelasi antara metacognitive awareness dan grammar achievement. Penelitian ini menggunakan metode korelasi dan melibatkan 87 mahasiswa semester satu program S1 dari Prodi Pendidikan Bahasa Inggris. Hasil analisis menunjukkan bahwa ada korelasi yang signifikan dan positif antara metacognitive awareness dan grammar achievement. Selain itu, evaluation diketahui sebagai prediktor yang paling dominan dan positif dalam memrediksi grammar achievement mahasiswa.